227k views
4 votes
If you could please help me? I have been having a really hard time so far. I would reallly appreciate if you could explain how to do the problems.

Thank you!

If you could please help me? I have been having a really hard time so far. I would-example-1
User Story
by
5.2k points

2 Answers

2 votes

I will set up question 1 and do question 2, which is easier to solve.

Question 1

To determine if a function is one-to-one, we must prove that f(a) = f(b). In other words, if you get the same y value by plugging a into the function as you do by plugging b, then the function is one-to-one. I will partially do the first one and let you do the rest on your own.

f(x) = (x - 1)/(3x + 3)

f(a) = (a - 1)/(3(a) + 3)

f(a) = (a - 1)/(3a + 3)

f(a) = (a - 1)/[3(a + 1)]

Now do f(b).

f(b) = (b - 1)/[3(b + 1)]

Set f(a) = f(b). If after doing the math you end up with a = b, then you will know that this function is one-to-one.

Take it from here and do the same for all functions listed.

Question 2

Let cbrt = cube root for short.

cbrt{x - 2} + 8

Let y = f(x)

y = cbrt{x- 2} + 8

Switch x and y.

x = cbrt{y - 2} + 8

x - 8 = cbrt{y - 2}

Cube both sides.

(x - 8)^3 = [cbrt{y - 2}]^3

(x - 8)^3 = y - 2

Solve for y.

(x - 8)^3 + 2 = y

Replace y with f^(-1) x.

f^(-1) x = (x - 8)^3 + 2

Answer: Choice 1

User Timothy Groote
by
5.2k points
7 votes

Answer:

2.

Explanation:

1. Recall the definition of one-to-one function. We say that
f is one-to-one if and only if the equality
f(a)=f(b) implies that
a=b.

First example:
f(x)=(x-1)/(3x+3).

We start with


f(a) = (a-1)/(3a+3) = (b-1)/(3b+3) = f(b).

In the above equalities, the central one, making cross products, is equivalent to


(a-1)(3b+3) = (3a+3)(b-1).

Then,
3ab+3a-3b-3 = 3ab-3a+3b-3. Now, cancelling identical terms we get
3a-3b=-3a+3b which is equivalent to
6a=6b. Thus, simplifying the factor 6, we get
a=b. Therefore, the function is one-to-one.

Second example:
f(x) = √(5x+9).

We try to follow the same reasoning. We start with


√(5a+9) = √(5b+9).

Now, we elevate both members to the square (recall that both expressions are positive, so there is no problem with squaring) and obtain:


5a+9=5b+9. We eliminate the 9's and we get
5a=5b. Simplifying the 5's, we finally obtain that
a=b. Therefore the function is one-to-one.

Third example.
f(x) = (7)/(4x^2).

This example is different from the previous ones. Recall that we prove that a function is not one-to-one if we find two different numbers
a\\eq b such that
f(a)=f(b).

Then, notice that if we take
a=-1 and
b=1 we get that


f(-1) = (7)/(4(-1)^2) = (7)/(4) and
f(-1) = (7)/(4\cdot 1^2) = (7)/(4).

Then, this function is not one-to-one.

Fourth example:
f(x) = (1)/(2)x^3.

As the first two cases. Consider
(1)/(2)a^3=(1)/(2)b^3. Then, simplify the factor 1/2, and we get
a^3=b^3.

Now, let us transform the previous equality into
a^3-b^3=0. This expression can be factored:
a^3-b^3=(a-b)(a^2+ab+b^2). Thus,


0=(a-b)(a^2+ab+b^2)

Notice that the above equality is possible if and only if
a-b=0 or


a^2+ab+b^2=0. But the second possibility is impossible (you can check it using the general formula for second degree equations), thus, necessarily
a-b=0 which is equivalent to
a=b. Therefore, the function is one-to-one.

Fifth example:
f(x) = 3x^4+7x^3.

First, notice that the polynomial
3x^4+7x^3 can be factored as


3x^4+7x^3 = x^3(3x+7).

From here is not difficult to deduce that
f(0)=0=f(-7/3) and consequently the function is not one-to-one.

2. As we are looking for the inverse function
f^(-1) of
f(x) is a better idea to use the following notation:


y = \sqrt[3]{x-2} + 8,

instead of
f(x).

Notice that, with this notation we are saying that
y depends on
x. Now, when we are looking for the inverse function we will try to write the variable
x in terms of
y. With this idea, the first step is to move the 8 in the right hand side to the left hand side, so:


y-8 = \sqrt[3]{x-2}.

Recall that we need to isolated the variable
x, so we must ‘‘eliminate’’ the cubic root. In order to do this we take cubic powers in both side of the above equality. Then,


(y-8)^3 = x-2.

Finally, we take the 2 to the left hand side and we get


x = (y-8)^3+2.

Thus, the inverse function is
f^(-1)(x) = (x-8)^3+2.

Notice that if we do
f(f^(-1)(x)) we get
x.

User Stefun
by
5.5k points